Persepsi Masyarakat Pengguna Jaminan Kesehatan Nasional (JKN) tentang Pelayanan Kesehatan Masyarakat di RSUD Dr. H. Slamet Martodirdjo Pamekasan Madura - Imamul Hakim, Dwi Marita Fitriana A.S (FALAH Jurnal Ekonomi Syariah, 2017)
This study aims to determine the public perception of health services that use the program of National Health Insurance in Dr. H. Slamet Martodirdjo Pamekasan Madura as well as the existence of BPJS Health itself. This type of research is descriptive quantitative. Methods of data collection in this study is to use questionnaires (questionnaires) and interviews. The sample in this research is obtained by purposive sampling method. Based on the existing criteria, obtained 168 respondents. Data analysis method is done by using likert scale, with data scoring analysis technique. Based on the results of data analysis from the existing sub-dimensions, some sub dimensions responded positively by the community, some sub dimensions responded to doubt / neutral such as the availability of drugs for patients BPJS, BPJS patient acceptance procedures, and sub dimensions of hospitality, courtesy. The best community response is in the Assurance dimension associated with the availability of a specialist physician with a score of 707 in the agreed category. Neutral response with the highest score of 570 is in the sub-dimension of the doctor trying to calm the patients anxiety about the illness suffered. In addition there is also a negative response that is in the sub Empathy (concern) related nurses spend a special time to communicate with patients score 404 in the category disagree. In addition to the sub dimensions of access (acess) related service personnel do not discriminate the patientâs economy responded negatively with a score of 398 in the category disagree.